O cuidado em saúde transgênero: decisões sobre a cirurgia de transgenitalização entre mulheres transexuais - Ciribelli, Carlos José de Moura (2020)
Transsexuality is an important theme in the field of gender studies, representing an area of constant theoretical and practical disputes between researchers, academics and activists. In Brazil, assistance to transsexual people in the public health service is structured through the Ministry of Health Ordinances that defined and expanded the Transsexualizing Process. Among the possibilities of procedures in the Transsexualizing Process, transgenitalization surgery has been an important part of the transition processes of some transsexual women. From a theoretical point of view, studies linked to Queer Theory are substantial in understanding transsexuality from a depathologizing conception of the transsexual experience and a critical view of social gender structures. Based on these points, the objective of the present study was to identify the interpretative repertoires used in decision processes related to transgenitalization surgery in the Transsexualizing Process among transsexual women who attend the integral health service to the transgender population. To this end, ten semi- structured interviews and audio-video recorded with transsexual women were conducted and these interviews were analyzed from the perspective of discourse analysis proposed by Discursive Psychology. Among the results, the interpretative repertoires identified were divided into three axes: repertoires that question transgenitalization surgery, repertoires that support transgenitalization surgery and repertoires that question and support transgenitalization surgery. The analysis of the repertoires allowed a discussion about the ideas, senses and meanings involved in transgenitalization surgery and made it possible to look at the place that surgery can occupy in the experience of transsexual women.